Battling time restrictions with collective discourse: collaborative quizzes in a condensed human anatomy course - Zi Guo; Natascha Heise (BMC Medical Education)
Abstract Background Undergraduate medical education is currently undergoing a remarkable period of transformation. The exponential growth of medical knowledge, accompanied by societal changes and expectations for the upcoming generation of physicians, is placing immense pressure on academic institutions to reform their curricula, particularly foundational courses such as human anatomy. Consequently, instructors are grappling with the challenge of striking a balance between a new curriculum and maintaining the time-honored benchmarks of medical education. Methods This study proposes a 9,5-week medical gross anatomy course containing collaborative quizzes to improve the efficacy in a condensed pre-clerkship curriculum. It was hypothesized that the implementation of collaborative quizzes facilitates group learning while ultimately helping students to be better prepared for the NBME (National Board of Medical Examiners) unit examinations used as summative assessment within the course. During the four collaborative quizzes, medical and medical masters student groups rotated through twenty dissected donor stations, each containing a short clinical or anatomy-related multiple-choice question formatted in NBME style. Students individually answered the question first and then collaboratively discussed the question in their group. Success was measured by individual student outcomes of four collaborative quizzes, two NBME anatomy-focused unit examinations, and overall course evaluations. Results Overall, all students (n = 203) passed the course and performed well on collaborative quizzes and NBME anatomy-focused unit examinations. Analysis of the quizzes revealed that questions involving tagged structures, blood supply, and nerves resulted in the most answer changes after group discussion. Course evaluations proved the collaborative quizzes to be enjoyable and beneficial to identify lack of knowledge areas. Conclusions To address time constraints within the pre-clerkship curricula effectively, it is crucial for educators to explore smaller adjustments to core learning principles. Collaborative quizzes in the gross anatomy laboratory provided students with opportunities to assess their knowledge in a low-stakes setting while simultaneously benefiting from peer learning. The collection and analysis of quiz grades offered a method of identifying struggling students before their first summative examination, enabling timely academic support. In the future, the research team hopes to continue using this assessment and integrate content from various other pre-clerkship courses.